Functions of Arp2/3 Complex in the Dynamics of Epithelial Tissues - Martin, Emmanuel; Suzanne, Magali (Frontiers in Cell and Developmental Biology, 2022)
Epithelia are sheets of cells that communicate and coordinate their behavior in order to ensure their barrier function. Among the plethora of proteins involved in epithelial dynamics, actin nucleators play an essential role. The branched actin nucleation complex Arp2/3 has numerous functions, such as the regulation of cell-cell adhesion, intracellular trafficking, the formation of protrusions, that have been well described at the level of individual cells. Here, we chose to focus on its role in epithelial tissue, which is rising attention in recent works. We discuss how the cellular activities of the Arp2/3 complex drive epithelial dynamics and/or tissue morphogenesis. In the first part, we examined how this complex influences cell-cell cooperation at local scale in processes such as cell-cell fusion or cell corpses engulfment. In the second part, we summarized recent papers dealing with the impact of the Arp2/3 complex at larger scale, focusing on different morphogenetic events, including cell intercalation, epithelial tissue closure and epithelial folding. Altogether, this review highlights the central role of Arp2/3 in a diversity of epithelial tissue reorganization.